Independent Component Analysis And Rough Fuzzy Based Approach To Web Usage Mining - Chimphlee, Siriporn; Salim, Naomie; Ngadiman, Mohd. Salihin; Chimphlee, Witcha; Srinoy, Surat (2006)

(untitled)
Web Usage Mining is that area of Web Mining which deals with the extraction of interesting knowledge from logging information produced by Web servers. A challenge in web classification is how to deal with the high dimensionality of the feature space. In this paper we present Independent Component Analysis (ICA) for feature selection and using Rough Fuzzy for clustering web user sessions. It aims at discovery of trends and regularities in web usersâ€™ access patterns. ICA is a very general-purpose statistical technique in which observed random data are linearly transformed into components that are maximally independent from each other, and simultaneously have â€œinterestingâ€ distributions. Our experiments indicate can improve the predictive performance when the original feature set for representing web log is large and can handling the different groups of uncertainties/ impreciseness accuracy.